Case Report: A case of occult insulinoma localized by [18F] FB (ePEG12)12-exendin-4 positron emission tomography with negative findings of selective arterial calcium stimulation test - Sakaki, Kentaro; Murakami, Takaaki; Fujimoto, Hiroyuki; Shimizu, Yoichi; Miyake, Kanae Kawai; Otani, Daisuke; Otsuki, Shinya; Shimizu, Hironori; Nagai, Kazuyuki; Nomura, Takumi; Yabe, Daisuke; Nakamoto, Yuji; et al. (Frontiers in Endocrinology, 2025)
BackgroundInsulinomas, the most common functional pancreatic neuroendocrine tumors, cause hypoglycemia due to excessive insulin production, leading to severe clinical symptoms like coma or death. Resection surgery is the major curative treatment, but preoperative localization is challenging due to their small size. Traditional imaging methods like computed tomography (CT) and magnetic resonance imaging (MRI) often fail to detect tumors, while more invasive procedures like endoscopic ultrasound tissue acquisition (EUS-TA) and the selective arterial calcium stimulation test (SACST), though informative, depend heavily on operator skill and may not always provide conclusive results. There is an urgent need for non-invasive, sensitive localization methods for insulinomas. Glucagon-like peptide 1 receptor (GLP-1R) targeted PET imaging has emerged as a promising tool. We present a clinical case where [18F] FB (ePEG12)12-exendin-4 positron emission tomography/CT (18F-exendin-4 PET/CT) successfully detected insulinoma, unachievable by conventional imaging, underscoring its potential in guiding minimally invasive surgery.Case descriptionA 67-year-old female developed hyperinsulinemic hypoglycemia but could not undergo surgery as conventional imaging methods failed to localize the insulinoma. She was managed with diazoxide for six years, but her symptoms worsened. At 73, she was referred to our hospital. CT, MRI, endoscopic ultrasound, and SACST failed to detect the tumor in any artery. However, 18F-exendin-4 PET/CT revealed a nodule with uptake in the dorsal pancreas, suspected to be the culprit lesion. The patient underwent surgery, and although the tumor appeared discontinuous with the pancreas macroscopically, histopathology confirmed it was microscopically continuous, identifying it as a primary pancreatic insulinoma. Post-surgery, she achieved complete remission of symptoms and fully recovered.DiscussionThis case demonstrates the utility of 18F-exendin-4 PET/CT, a novel GLP-1 receptor-targeted imaging technique, in accurately localizing an occult insulinoma even with negative findings of SACST, enabling minimally invasive curative surgery.ConclusionThe 18F-exendin-4 PET/CT successfully localized an insulinoma undetectable by other methods, enabling minimally invasive curative resection. This technique offers a valuable diagnostic option for enabling minimally invasive surgery in occult insulinoma cases.